2019
DOI: 10.33423/jaf.v19i4.2177
|View full text |Cite
|
Sign up to set email alerts
|

Gen Z: Exploring Service Learning Projects in Managerial Accounting

Abstract: Service learning projects capitalize on the unique characteristics of Gen Z students and meet the requirements of the American Institute of Certified Public Accountants' (AICPA) core competencies. This project not only increased students' soft skills, making them more marketable to future employers, but also made a difference in the lives of the people served. Participants mastered managerial accounting topics through hands-on experiences that are often considered complex to grasp, which instilled inspiration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Research found SL promoted the positive learning outcomes of students, such as profession skills, communication skills, and collaboration. (Anderson et al, 2019;Leon et al, 2017;Lovat & Clement, 2016;Popovich & Brooks-Hurst, 2019;Pratt & Danyluk, 2017;Edmond & Driskill, 2019). So did the study find.…”
Section: Pre-service Teacher Educationmentioning
confidence: 84%
“…Research found SL promoted the positive learning outcomes of students, such as profession skills, communication skills, and collaboration. (Anderson et al, 2019;Leon et al, 2017;Lovat & Clement, 2016;Popovich & Brooks-Hurst, 2019;Pratt & Danyluk, 2017;Edmond & Driskill, 2019). So did the study find.…”
Section: Pre-service Teacher Educationmentioning
confidence: 84%